2007
DOI: 10.1002/jcp.21264
|View full text |Cite
|
Sign up to set email alerts
|

Gab2 requires membrane targeting and the met binding motif to promote lamellipodia, cell scatter, and epithelial morphogenesis downstream from the met receptor

Abstract: Gab1 and Gab2 are conserved scaffolding proteins that amplify and integrate signals stimulated by many growth factor receptors including the Met receptor. Gab1 acts to diversify the signal downstream from Met through the recruitment of multiple signaling proteins, and is essential for epithelial morphogenesis. However, whereas Gab1 and Gab2 are both expressed in epithelial cells, Gab2 fails to support a morphogenic response. We demonstrate that Gab1 and Gab2 are divergent in their function whereby Gab1, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
(132 reference statements)
2
6
0
Order By: Relevance
“…Following Gab1 knockdown in MKN45 cells or in fibroblasts expressing a Tpr-Met mutant unable to recruit Gab1 Y1349F/Y1356FY, the inability to produce invadopodia and/or actin rosettes (Figs 3, 4) is due to decreased assembly of actin-rich core structures (supplementary material Movies 2,3), consistent with a role for Met-Gab1 signaling in the regulation of an early step in invadopodia formation. This supports previous reports that Gab1 plays a role in Met-dependent regulation of other actin-rich cellular structures, such as lamellipodia (Frigault et al, 2008) and circular dorsal ruffles (Abella et al, 2010). Hence, depending on the cellular context, Gab1 provides a common link between Met signals and assembly of actin-rich structures at the cell periphery.…”
Section: Discussionsupporting
confidence: 92%
“…Following Gab1 knockdown in MKN45 cells or in fibroblasts expressing a Tpr-Met mutant unable to recruit Gab1 Y1349F/Y1356FY, the inability to produce invadopodia and/or actin rosettes (Figs 3, 4) is due to decreased assembly of actin-rich core structures (supplementary material Movies 2,3), consistent with a role for Met-Gab1 signaling in the regulation of an early step in invadopodia formation. This supports previous reports that Gab1 plays a role in Met-dependent regulation of other actin-rich cellular structures, such as lamellipodia (Frigault et al, 2008) and circular dorsal ruffles (Abella et al, 2010). Hence, depending on the cellular context, Gab1 provides a common link between Met signals and assembly of actin-rich structures at the cell periphery.…”
Section: Discussionsupporting
confidence: 92%
“…Membrane targeting of Gab1 plays a critical role in mediating tyrosine kinase receptors-triggered signaling [24, 25]. To show Gab1 subcellular localization in the cell-cell contacts by both flow and HGF, we infected HUVECs with adenoviral GFP-tagged Gab1 (Ad-GFP-Gab1) followed by exposure to flow or treatment with HGF for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…As already discussed above, the generation of knock-in -mice carrying mutations in either the SHP2 or the p85 binding sites of Gab1 revealed that these interactions play distinct roles in embryonic development [32]. Interestingly, enforced membrane localization of Gab2 through the addition of a myristoylation signal together with the introduction of the MBD from Gab1 is sufficient to confer a Gab1-like behaviour to Gab2 in HGF-stimulated MDCK cells [146]. These findings indicate that in the case of Gab1 and Gab2, differences in their subcellular compartmentalization, rather than in coupling to effectors, leads to distinct biological properties.…”
Section: Physiological Functions Of Gab Proteinsmentioning
confidence: 99%